Effect of precursor and calcination time on the morphological structure and catalytic activity of Co\(_{3}\)O\(_{4}\) film in the oxygen evolution reaction - Nguyen Thi , Giang; Pham Hong, Hanh; Ngo Thi Anh , Tuyet; Vu Thi Kim , Oanh; Do, Linh; Nguyen Duc, Lam; Nguyen Thi, Mai; Bui, Hoa; Nguyen Thanh , Tung (Communications in Physics, 2024)
This research investigates the effect of cobalt precursor and calcination time on the morphology and catalytic activity of Co\(_{3}\)O\(_{4}\) films in the oxygen evolution reaction. Co\(_{3}\)O\(_{4}\) films with porous flower-like nanostructures were obtained using cobalt nitrate as a cobalt precursor, while cobalt chlorides were used to produce porous nanoneedle structures Co\(_{3}\)O\(_{4}\) film. Extended annealing time at temperature 350\r{}C caused structural fractures in the films. Among the samples, the synthesized Co\(_{3}\)O\(_{4}\) films were then evaluated as catalyst materials for the oxygen evolution reaction in alkaline 1M KOH electrolyte. Among synthesized films, the Co\(_{3}\)O\(_{4}\)-2-1h, synthesized using the cobalt chlorides as Co precursor and annealed at 350\r{}C for 1 hour, exhibited better oxygen evolution reaction catalytic activity. With its porous nanoneedle structure, the Co\(_{3}\)O\(_{4}\)-2-1h demonstrated superior performance comparable to the state-of-the-art 20% Ir/C catalyst. Moreover, the Co\(_{3}\)O\(_{4}\)-2-1h film \copyediting{demonstrates}{demonstrated} remarkable stability for the oxygen evolution reaction in a 1M KOH alkaline electrolyte.